Effect of the winter diet on meat quality traits of steers finished on mountain pasture with a barley supplement - Panea, B.; Casasús, I.; Joy, M.; Carrasco, S.; Ripoll, G.; Albertí, P.; Blanco, M. (Spanish Journal of Agricultural Research, 2012)
The aim of this study was to evaluate the effect of two winter diets (WD) (100 F, i.e. 100% forage, 8.3 kg DM of lucerne hay + 0.3 kg DM of straw; and 65F:35C, i.e. 65% forage:35% concentrate, 5.4 kg DM lucerne hay + 0.3 kg DM straw + 3.0 kg DM barley), offered during 118 days on meat quality traits of 20-month old steers finished on mountain pasture supplemented with 4.1 kg DM barley d-1. Longissimus thoracis intramuscular fat content and its fatty acid profile were determined (in vivo) after one month on pasture. The intramuscular fat content, fatty acid profile, texture (1, 8 and 15 days of ageing), colour (1, 2, and 8 days of oxygen exposure) and sensorial quality (8 and 15 days ageing) were evaluated post-mortem after 163 days on the finishing diet. Intramuscular fat content and fatty acid profile were affected by the WD in vivo (p<0.05) but not post-mortem. Meat pH was not affected by the WD but the texture was affected by the interaction between the WD and the ageing time (p<0.001), maximum stress decreased more rapidly in the 100F diet in the first 8 days of ageing. Meat colour was only affected by the oxygen-exposure time (p<0.001). Panel test variables were not affected by the WD, but ageing time affected beef flavour intensity (p<0.05). In conclusion, the winter diet affected intramuscular fat content after one month of grazing but had no major effects on post-mortem meat quality of pasture-finished steers.